Neurovascular Alterations in Vascular Dementia: Emphasis on Risk Factors - Lecordier, Sarah; Manrique-Castano, Daniel; El Moghrabi, Yara; ElAli, Ayman (Frontiers in Aging Neuroscience, 2021)
Vascular dementia (VaD) constitutes the second most prevalent cause of dementia in the world after Alzheimer’s disease (AD). VaD regroups heterogeneous neurological conditions in which the decline of cognitive functions, including executive functions, is associated with structural and functional alterations in the cerebral vasculature. Among these cerebrovascular disorders, major stroke, and cerebral small vessel disease (cSVD) constitute the major risk factors for VaD. These conditions alter neurovascular functions leading to blood-brain barrier (BBB) deregulation, neurovascular coupling dysfunction, and inflammation. Accumulation of neurovascular impairments over time underlies the cognitive function decline associated with VaD. Furthermore, several vascular risk factors, such as hypertension, obesity, and diabetes have been shown to exacerbate neurovascular impairments and thus increase VaD prevalence. Importantly, air pollution constitutes an underestimated risk factor that triggers vascular dysfunction via inflammation and oxidative stress. The review summarizes the current knowledge related to the pathological mechanisms linking neurovascular impairments associated with stroke, cSVD, and vascular risk factors with a particular emphasis on air pollution, to VaD etiology and progression. Furthermore, the review discusses the major challenges to fully elucidate the pathobiology of VaD, as well as research directions to outline new therapeutic interventions.